Molecular markers reveal reproductive strategies of non-pollinating fig wasps - Cook, JM; Reuter, C; Moore, JC; West, SA (Wiley, 2017)
1. Fig wasps have proved extremely useful study organisms for testing how reproductive decisions evolve in response to population structure. In particular, they provide textbook examples of how natural selection can favour female-biased offspring sex ratios, lethal combat for mates and dimorphic mating strategies. 2. However, previous work has been challenged, because supposedly single species have been discovered to be a number of cryptic species. Consequently, new studies are required to determine population structure and reproductive decisions of individuals unambiguously assigned to species. 3. Microsatellites were used to determine species identity and reproductive patterns in three non-pollinating Sycoscapter species associated with the same fig species. Foundress number was typically one to five and most figs contained more than one Sycoscapter species. Foundresses produced very small clutches of about one to four offspring, but one foundress may lay eggs in several figs. 4. Overall, the data were a poor match to theoretical predictions of solitary male clutches and gregarious clutches with n-1 females. However, sex ratios were male-biased in solitary clutches and female-biased in gregarious ones. 5. At the brood level (all wasps in a fig), a decrease in sex ratio with increasing brood size was only significant in one species, and sex ratio was unrelated to foundress number. In addition, figs with more foundresses contain more wasp offspring. 6. Finally, 10-22% of females developed in patches without males. As males are wingless, these females disperse unmated and are constrained to produce only sons from unfertilised eggs.